Intermittent Parathyroid Hormone After Prolonged Alendronate Treatment Induces Substantial New Bone Formation and Increases Bone Tissue Heterogeneity in Ovariectomized Rats. (13th June 2017) - Altman‐Singles, Allison R; Jeong, Yonghoon; Tseng, Wei‐Ju; de Bakker, Chantal MJ; Zhao, Hongbo; Lott, Carina; Robberts, Juhanna; Qin, Ling; Han, Lin; Kim, Do‐Gyoon; Liu, X Sherry
ABSTRACT: Postmenopausal osteoporosis is often treated with bisphosphonates (eg, alendronate, [ALN]), but oversuppression of bone turnover by long‐term bisphosphonate treatment may decrease bone tissue heterogeneity. Thus, alternate treatment strategies after long‐term bisphosphonates are of great clinical interest. The objective of the current study was to determine the effect of intermittent parathyroid hormone (PTH) following 12 weeks of ALN (a bisphosphonate) treatment in 6‐month‐old, ovariectomized (OVX) rats on bone microarchitecture, bone remodeling dynamics, and bone mechanical properties at multiple length scales. By using in vivo μCT and 3D in vivo dynamic bone histomorphometry techniques, we demonstrated the efficacy of PTH following ALN therapy for stimulating new bone formation, and increasing trabecular thickness and bone volume fraction. In healthy bone, resorption and formation are coupled and balanced to sustain bone mass. OVX results in resorption outpacing formation, and subsequent bone loss and reduction in bone tissue modulus and tissue heterogeneity. We showed that ALN treatment effectively reduced bone resorption activity and regained the balance with bone formation, preventing additional bone loss. However, ALN treatment also resulted in significant reductions in the heterogeneity of bone tissue mineral density and tissue modulus. On the other hand, PTH treatment was able to shift the bone remodeling balance in favor of formation, with or without a prior treatment with ALN. Moreover, by altering the tissue mineralization, PTH alleviated the reduction in heterogeneity of tissue material properties induced by prolonged ALN treatment. Furthermore, switching to PTH treatment from ALN improved bone's postyield mechanical properties at both the whole bone and apparent level compared to ALN alone. The current findings suggest that intermittent PTH treatment should be considered as a viable treatment option for patients with prior treatment with bisphosphonates. © 2017 American Society for Bone and Mineral Research.